Growth of the Barents Sea capelin (Mallotus villosus) in relation to climate - Gjøsæter, Harald; Loeng, Harald (ICES, 1986)
The history of capelin assessment in the Barents Sea has shown that the growth of individual capelin has varied between years and different parts of the capelin distribution area. As the number of individuals in this stock is very high, even small changes in individual growth will affect the surplus production and the catches which may be taken from it. If this growth could be estimated in advance, the assessment could be made more precise. Temperature variation has been suggested as a factor which could be partly responsible for the variation in growth. To study this possibility, we compared corresponding values of temperature and length increment of the capelin in different parts of the Barents Sea from 1976 to 1985. The mean temperature in subareas was calculated by averaging the temperatures for the depth interval 10-200 m at all of the hydrographical stations taken each September in each statistical square which the sea is devided, and then combining the squares to form subareas. The estimates of growth were calculated by substracting the backcalculated length corresponding to the outermost winter ring in the otolith from the length at sampling. A positive covariance between water temperature and growth was indicated when all the material was considered, but no clear correspondance was found between temperature and growth within subareas.